Pengembangan Model Pembelajaran Berbasis Sistem Informasi SIPETA untuk Menganalisis Progres Estetika dan Teknik Karya Seni Mahasiswa PPG Seni Budaya sebagai Dasar Refleksi Akademik dan Supervisi Kurikulum - Prasetyo, Abdul Rahman; Fajarianto, Otto; Kusumaningrum, Shirly Rizki (EduInovasi: Journal of Basic Educational Studies, 2025)
The development of a learning model based on the SIPETA information system (Information System for Aesthetic Assessment and Artistic Engineering) was carried out to answer the need for objective and reflective academic supervision in arts and culture education, especially in the Teacher Professional Program (PPG). The main goal of this study is to present a digital system that is able to systematically record and analyze the progress of students' artworks and techniques as a basis for decision-making in curriculum development. The method used is a Research and Development approach with the ADDIE model which focuses on the initial three stages: analysis, design, and development. Data were collected through interviews with lecturers, studio class observations, and literature reviews and portfolios of student work. The results of the analysis show that conventional assessments are still subjective and poorly documented. The SIPETA system is designed with excellent features such as uploading digital works, technical-aesthetic assessment rubrics, progress timelines, visual feedback, and evaluation dashboards. Validation shows that this system is feasible to use in the context of learning art practice. The results of the development show that SIPETA is able to significantly improve the quality of students' academic evaluation and reflection. In conclusion, the SIPETA learning model has the potential to be a data-based curriculum supervision tool, strengthen academic transparency, and encourage digital transformation in adaptive and sustainable arts education.